PENGARUH PENAMBAHAN SUSU SKIM TERHADAP KARAKTERISTIK YOGHURT JAGUNG MANIS (Zea Mays L. Saccharata) - Wisesa Diputra, Komang; Puspawati, Ni Nyoman; Indri Hapsari A., Ni Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 5 No 2 (2016): Jurnal ITEPA)
This research aimed to determine the effect of skim milk on the characteristics of sweet corn yogurt and to determine the concentration of skim milk which is capable of producing sweet corn yogurt with the best characteristics. This research uses random design by treatment with the addition of skim milk, which consists of five levels, 5%, 7.5%, 10%, 12.5%, and 15%.The percentage on the addition of skim milk which is calculated from the volume of milk corn used.Treatment was repeated three times to obtain 15 units of sample. Data were analyzed by analysis of variance followed by multiple comparison test of Duncan Multiple Range Test (DMRT).The variables measured were the levels of protein, fat, ash content, total lactic acid bacteria (LAB), the degree of acidity or pH, total acid titration (TAT), flavor, color, aroma, texture and overall acceptance. The addition of 12.5% skim milk was able to produce the best characteristics of sweet corn yogurt with 2.13% protein content, 2.22% fat content, 0.91% ash content, 8.5x10 9 CFU/ml total lactic acid bacteria, pH 3.82, 1.63% total acid, color rather like and yellow, aroma rather like and rather typical corn, texture rather like and slightly thick, flavour like and rather typical corn and overall acceptance rather like.
Keywords: yogurt, skim milk, sweet corn